(untitled) (Eureka Journal of Education & Learning Technologies, 2026)
This article analyzes young people’s understanding of the ethnopsychological characteristics and values of the Uzbek family. It highlights how these young people can widely apply our national traditions and values in their future family lives, ensuring they are preserved and passed down from generation to generation.